2022
DOI: 10.2967/jnumed.122.264069
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Early68Ga-FAPI PET Acquisition Comparing68Ga-FAPI-02,68Ga-FAPI-46, and68Ga-FAPI-74: Methodologic and Diagnostic Implications for Malignant, Inflammatory/Reactive, and Degenerative Lesions

Abstract: Ga-labeled fibroblast activation protein (FAP) inhibitor ( 68 Ga-FAPI) PET targets 68 Ga-FAPI-positive activated fibroblasts and is a promising imaging technique for various types of cancer and nonmalignant pathologies. However, discrimination between malignant and nonmalignant 68 Ga-FAPI-positive lesions based on static PET with a single acquisition time point can be challenging. Additionally, the optimal imaging time point for 68 Ga-FAPI PET has not been identified yet, and different 68 Ga-FAPI tracer varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Since FAP inhibitors (FAPIs) are potentially useful for cancer therapy, FAP may also serve as a unique tumor-specific biomarker for diagnosis and therapy . Recent discoveries of radiolabeled FAPI derivatives have demonstrated high potential in cancer theranostics, and many clinical studies of FAPI tracers have been reported in the literature. Among these reported FAPI imaging agents, [ 68 Ga]­Ga-DOTA-FAPI-04 (Figure ) is the most well-studied front runner. , …”
Section: Introductionmentioning
confidence: 99%
“…Since FAP inhibitors (FAPIs) are potentially useful for cancer therapy, FAP may also serve as a unique tumor-specific biomarker for diagnosis and therapy . Recent discoveries of radiolabeled FAPI derivatives have demonstrated high potential in cancer theranostics, and many clinical studies of FAPI tracers have been reported in the literature. Among these reported FAPI imaging agents, [ 68 Ga]­Ga-DOTA-FAPI-04 (Figure ) is the most well-studied front runner. , …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that image acquisition earlier than 60 minutes or even multiple-minute time points improve the discrimination of malignant lesions. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that image acquisition earlier than 60 minutes or even multiple-minute time points improve the discrimination of malignant lesions. 23,24 The strength of the reported study is the 1:1 correlation of localization and histological confirmation of suspicious LNs by performing laparoscopic nodal staging after [ 68 Ga]Ga-FAPI-46 PET/CT and [ 18 F] F-FDG PET/CT. This study benefits from the fact that patients were in RT positioning, and immobilization devices were used for all imaging data (better comparability of both scans).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, FAP inhibitors (FAPIs) have become a new targeted molecular probe in nuclear medicine and have attracted much attention in cancer diagnosis and treatment. Currently, dozens of radiopharmaceuticals targeting FAP have been developed, such as FAPI-01, FAPI-2, FAPI-04, FAPI-42, FAPI-46, and FAPI-74 (15)(16)(17)(18). In a recent study, high-quality images were obtained using gallium-68-FAPI-04 positron emission tomography/computed tomography ( 68 Ga-FAPI-04 PET/CT) showing good biodistribution properties and a high tumor background ratio in 28 tumors, including abdominal and pelvic tumors (19).…”
Section: Introductionmentioning
confidence: 99%